Implementasi Tari Kreasi untuk Meningkatkan Kecerdasan Kinestetik Anak - Abd. Hakim Naba; Nirwana Nirwana (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2021)
Abstrak: Implementation of Creation Dance to Improve Children's Kinesthetic Intelligence. This study aims to describe the implementation of dance creations to improve children's intelligence. This research belongs to the type of qualitative research. The subjects of this study were students of group B aged 5-6 years TK IT Al-Fikri Makassar. The data collection techniques used in this study were observation, interviews, and documentation. Data analysis techniques use caulitative descriptive analysis. The results of this study show that dance creation can develop children's kinesthetic intelligence according to expectations.